Trends in planktonic copepod diversity in reservoirs and lotic stretches in a large river basin in South America - Perbiche-Neves, Gilmar; Boxshall, Geoffrey A.; Nogueira, Marcos G. [UNESP]; Rocha, Carlos E. F. da (Csiro Publishing, 2014)
Copepod assemblages were analysed across La Plata River basin, the second largest in South America. High values of species richness and Shannon-Wiener diversity were found in the lower Parana River, the main and largest river of the basin, and in eutrophic reservoirs located in the upper basin. The species richness was negatively correlated with turbidity, probably because of the negative impact on filtration rates in calanoids. There was a trend of decreasing richness correlated with high water flow in reservoirs with short water-retention time (<40 days) and simple morphometric shape, and also in deeper oligo-mesotrophic reservoirs with very long water-retention time and dendritic shape (variables that occurred in combination in the present study). The number of copepod species (46) found in our study is only about half of the gamma diversity estimated using Jack1 non-parametric analysis for the basin (86 species). There are groups of copepod species typical of reservoirs and rivers, and others that can occur in both of these habitat types. Reservoir and lentic species are favoured by a deeper water column, higher temperatures and higher transparency, whereas the opposite is the case of typical riverine species. There is also a group of species that occur in both sets of conditions.
Keywords: crustaceans; diversity; ecology; freshwater; lentic; limnology; running water